Characterization antibacterial constituent from Ficus deltoideusJack leaves - Suryati .; Hazli Nurdin; Dachriyanus .; Md Nordin Hj Lajis (Indonesian Journal of Pharmacy, 2010)
An antibacterial constituent, has been isolated from Ficus deltoideus Jack leaves. Based on spectroscopic data (IR, 1H-NMR, 13 C NMR 1D and 2D and MS), the structure of this compound was identified as Olean-12en-3β-ol, (β-amyrin), C30H50O. This compound showed antibacterial activities against E. coli, B. subtilis and S.  aureus.  The minimum inhibition concentration (MIC) agains  E.  coli,  B. subtilisand  S. aureusare 230, 380 and 460 (µg/mL) respectively.Key words: Antibacterial activity,Ficus deltoideusJack, β-amyrin